Procurement and supply chain management in government institutions: A case study of select departments in the Limpopo Province, South Africa - Madira R. Selomo; Krishna K. Govender (Dutch Journal of Finance and Management, 2016)
The current state of the South African (SA) government's Supply Chain Management (SCM) is fraught with malpractices which include lack of good governance, fair, equitable, transparent, competitive and cost-effective procurement process. In light of the aforementioned, this paper reports on a study which examined SCM performance, more specifically, procurement management in select provincial government departments in SA. The aim of this exploratory study on which this paper is written, is to determine how procurement planning, execution, control, and monitoring affect SCM performance. Data was collected using self-administered questionnaires which were personally distributed and collected by the primary researcher, from four Limpopo Provincial government departments which were purposively selected. The Statistical Package for Social Sciences (SPSS) was used to analyse the data. Generally, SCM performance in the various surveyed government departments is effective, although it became evident that the departments experience obstacles during the implementation of SCM processes and procedures. Furthermore, procurement planning is inadequate and needs improvement when the departments procure goods, services or works. Procurement execution was also found wanting, especially with regards to procurement governance. The results of this study may assist the participating departments to align their SCM and procurement practices to prescribed legislation in order to increase SCM performance, as well as achieve the objectives of good governance in terms of the Green Paper on Public Sector Procurement Reform in South Africa.
Keywords: 650; procurement; public procurement; supply chain management; governance